2018
DOI: 10.1051/kmae/2018014
|View full text |Cite
|
Sign up to set email alerts
|

Global distribution and climatic match of a highly traded ornamental freshwater fish, the sailfin mollyPoecilia latipinna(Lesueur, 1821)

Abstract: Predicting alien species' establishment through climate matching may inform management actions preventing future invasions. The aim of the current study was to evaluate the climate match of the sailfin molly (Poecilia latipinna) worldwide, with emphasis on Europe and the Mediterranean. A literature review indicated that the species presents a total of 100 non-indigenous occurrences in 29 countries worldwide. Predominantly, it has been introduced within tropical/subtropical climatic zones, where it is usually c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
(68 reference statements)
0
2
0
1
Order By: Relevance
“…Fertilized eggs develop into embryos around three to four weeks, and reproduction is repeated every eight to ten weeks, depending on typical environmental conditions (Wischnath, 1993;Yamamoto & Tagawa, 2000). Molly fish have been introduced to tropical and subtropical regions in more than 29 countries around the world, either for biological control of mosquitoes or for commercial purposes (Koutsikos et al 2018). For the characteristics of this species, it is considered a typical model for molecular studies.…”
Section: Sailfin Mollymentioning
confidence: 99%
“…Fertilized eggs develop into embryos around three to four weeks, and reproduction is repeated every eight to ten weeks, depending on typical environmental conditions (Wischnath, 1993;Yamamoto & Tagawa, 2000). Molly fish have been introduced to tropical and subtropical regions in more than 29 countries around the world, either for biological control of mosquitoes or for commercial purposes (Koutsikos et al 2018). For the characteristics of this species, it is considered a typical model for molecular studies.…”
Section: Sailfin Mollymentioning
confidence: 99%
“…It is native to the northeastern coasts of the USA and South America (Markle, 2015). It was introduced to many countries and has been recorded in 29 countries mainly in Asia, Oceania and Central and South America (Koutsikos et al, 2018). P. latipinna has been introduced to some countries in the Middle East, such as Iraq, where it has been recorded in the southern marshes (Hussain et al, 2009), P. latipinna is considered an ornamental fish and can survive in a temperature range of 20-26 °C and a pH range of 7.5-8.5.…”
Section: Introductionmentioning
confidence: 99%
“…This has been found to be especially true for escaped ornamental fish. For example, Koutsikos et al (2018) showed that the non‐native distribution of the sailfin molly, Poecilia latipinna , is determined primarily by water temperature. More broadly, across aquatic systems, Moyle and Light (1996a) argued that if individuals have survived and established beyond initial introduction, abiotic conditions usually are assumed to be appropriate for the invading species.…”
Section: Introductionmentioning
confidence: 99%